One Health Consensus Report Annotation Checklist (OH‐CRAC): A cross‐sector checklist to support harmonized annotation of surveillance data in reports. (22nd June 2022) - Lopez de Abechuco, Estibaliz; Dórea, Fernanda; Buschhardt, Tasja; Scaccia, Nazareno; Günther, Taras; Foddai, Alessandro; Dups‐Bergmann, Johanna; Filter, Matthias
Abstract: To facilitate cross‐sector integration of surveillance data it is necessary to improve and harmonize the meta‐information provided in surveillance data reports. Cross‐sector integration of surveillance results in sector‐specific reports is frequently difficult as reports with a focus on a single sector often lack aspects of the relevant meta‐information necessary to clarify the surveillance context. Such reporting deficiencies reduce the value of surveillance reports to the One Health community. The One Health Consensus Report Annotation Checklist (OH‐CRAC), described in this paper along with potential application scenarios, was developed to improve the current practice of annotating data presented in surveillance data reports. It aims to provide guidance to researchers and reporting officers on what meta‐information should be collected and provided to improve the completeness and transparency of surveillance data reports. The OH‐CRAC can be adopted by all One Health‐related sectors and due to its cross‐sector design, it supports the mutual mapping of surveillance meta‐information from sector‐specific surveillance reports on federal, national and international levels. To facilitate the checklist completion, OH‐CRAC is also available as an online resource that allows the collection of surveillance meta‐information in an easy and user‐friendly manner. Completed OH‐CRAC checklists can be attached as annexes to the corresponding surveillance data reports or even to individual data files regardless of the data source. In this way, reports and data become better interpretable, usable and comparable to information from other sectors, improving their value for all surveillance actors and providing a better foundation for advice to risk managers.